Rethinking Statehood in Palestine Self-Determination and Decolonization Beyond Partition - Farsakh, Leila H. (University of California Press, 2021)
The quest for an inclusive and independent state has been at the center of the Palestinian national struggle for a very long time. This book critically explores the meaning of Palestinian statehood and the challenges that face alternative models to it. Giving prominence to a young set of diverse Palestinian scholars, this groundbreaking book shows how notions of citizenship, sovereignty, and nationhood are being rethought within the broader context of decolonization. Bringing forth critical and multifaceted engagements with what modern Palestinian self-determination entails, Rethinking Statehood sets the terms of debate for the future of Palestine beyond partition. "At a juncture when independent Palestinian statehood seems unachievable, these astute reflections are particularly welcome. They offer innovative suggestions for how to provide renewed dynamism to the Palestinian struggle, outside the confines of a two-state solution that has been systematically sabotaged by Israel for over fifty years." RASHID KHALIDI, author of The Hundred Years' War on Palestine "Rethinking Statehood in Palestine breaks new analytical ground on urgent issues. It is also theoretically rich for more general explorations of the nation-state, citizenship, justice, and the efficacy (or not) of international legal mechanisms in addressing injustice." PENNY JOHNSON, coeditor of Seeking Palestine: New Writings on Home and Exile "This book provides crucial answers to the challenges facing the Palestinians and new insight into the nature of the relationship between national liberation, human liberation, and state-building." ALAIN GRESH, author of The PLO: The Struggle Within and cofounder of Orient XXI